2022
DOI: 10.18502/jabs.v11i2.8765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress-Induced Glucocorticoids on Reproductive Dysfunction in Men

Abstract: There are different factors affecting the reproductive fitness of organisms, such as the ecological and environmental factors, resource availability, and stress within their habitat. The challenging incidents in the organism’s environment result in activation of the response system of central stress mediated with the hypothalamic-pituitary-adrenal (HPA) axis. This axis’s regulatory function controls such items as immune and cardiovascular functions, metabolisms, and reproductive system. Its activation shows re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This delicate hormonal balance can be disturbed by stress, leading to impaired male fertility. Nateghian, Aliabadi, and Aliabadi (2022) has also shown that psychological stress can exacerbate oxidative stress, which is associated with DNA damage in sperm. This can cause a decrease in semen volume, sperm concentration, and sperm motility, making it more difficult for sperm to reach and fertilize the egg.…”
Section: Discussionmentioning
confidence: 99%
“…This delicate hormonal balance can be disturbed by stress, leading to impaired male fertility. Nateghian, Aliabadi, and Aliabadi (2022) has also shown that psychological stress can exacerbate oxidative stress, which is associated with DNA damage in sperm. This can cause a decrease in semen volume, sperm concentration, and sperm motility, making it more difficult for sperm to reach and fertilize the egg.…”
Section: Discussionmentioning
confidence: 99%